ESTUDO DOS PERFIS DE SOLICITAÇÃO E VELOCIDADES DE ENSAIO NA AVALIAÇÃO REOLÓGICA POR REOMETRIA ROTACIONAL - Costa, Ana Rita Damasceno; Silva, Francisco Gabriel Santos; Silva, Vanessa Silveira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The rheological study of pastes and mortars by rotational rheometry does not have a brazilian normative prescription that defines the test parameters. It hampers the definition of a standardized method, in order to leave the evaluation variables such as torque and frequency at the researcher’s charge, often becoming an obstacle to comparison of results. In this work, rheological behavior of cement-lime based mortars with and without air entraining admixture was evaluated by means of rotational rheometry using level profile, ladder and ascending-descending. The results of the studied profiles have shown differences in rheological parameters of yield stress. The ladder profile was the most suitable for mortars containing air-entraining admixture because, due to the shorter test time, there was less air incorporation during rheometry, thereby reducing the influence of the test method on the evaluated properties. The ladder profile was also the most suitable for mortars without admixtures, since the test time did not allow the sedimentation of the particles as well as their influence on the rheological behavior of mortar.